2002
DOI: 10.1128/iai.70.9.5246-5255.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Siderophore Iron Transporter ofCandida albicans(Sit1p/Arn1p) Mediates Uptake of Ferrichrome-Type Siderophores and Is Required for Epithelial Invasion

Abstract: The human fungal pathogen Candida albicans contains a close homologue of yeast siderophore transporters, designated Sit1p/Arn1p. We have characterized the function of SIT1 in C. albicans by constructing sit1 deletion strains and testing their virulence and ability to utilize a range of siderophores and other iron complexes. sit1 mutant strains are defective in the uptake of ferrichrome-type siderophores including ferricrocin, ferrichrysin, ferrirubin, coprogen, and triacetylfusarinine C. A mutation of FTR1 did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(182 citation statements)
references
References 51 publications
5
169
1
2
Order By: Relevance
“…Hemin, used as an independent control, could also restore the growth of the ⌬ftr1⌬ftr2 mutant strain, as it did with the ⌬sit1/arn1 mutant strain. This result is consistent with previous studies that suggested a distinct uptake pathway for hemin (5,18). Susceptibility of Candida albicans ⌬sit1/arn1 mutant strain to siderophore-drug conjugates.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Hemin, used as an independent control, could also restore the growth of the ⌬ftr1⌬ftr2 mutant strain, as it did with the ⌬sit1/arn1 mutant strain. This result is consistent with previous studies that suggested a distinct uptake pathway for hemin (5,18). Susceptibility of Candida albicans ⌬sit1/arn1 mutant strain to siderophore-drug conjugates.…”
Section: Resultssupporting
confidence: 83%
“…We can speculate that the ability of conjugates to perform well in an iron-deficient environment similar to that found at the mucosal surface of the mammalian host (17) and the ability of the conjugates to associate with Candida cells through high-affinity iron-transport receptors may represent valuable properties of antimicrobial molecules during therapy. This is supported by the results of Heymann et al (5) showing that the ferrichrome receptor CaSit1/CaArn1 was required for epithelial invasion and by the finding that high-affinity transport systems have been shown to transport specific substrates more efficiently into cells than simple diffusion when the concentration of the substrate outside the microbial cells is low (12), a situation that may occur between doses of antibiotics in a therapeutic regimen.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We also included an additional 15 ironrelated genes that showed Cap2-dependent up-regulation (six genes) or down-regulation (nine genes), for which the L_H_Fe data were not available. Interestingly, eight of the 18 up-regulated genes in the CAP2/cap2⌬ data have been shown experimentally to be involved in iron uptake pathways, viz., SIT1 encoding siderophore transporter (72) , FET3, FTR1, FRP1, CFL5, and FRE9 encoding reductive iron uptake (73,74), and RBT5 and HMX1 being part of heme uptake (35,75,76) pathways (Fig. 4C).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…Este fato é corroborado pelos relatos de que o transporte de sideróferos é requerido no processo especifico de infecção, denominado "invasão epitelial e penetração por Cândida albicans" (Heymann et al, 2002;Hu et al, 2002). Considerando que as vias biosintéticas de sideróferos são ausentes em células humanas, as vias de biosíntese de sideróferos em organismos patogênicos representam fortes candidatos a alvos de agentes quimioterápicos (Eisendle et al, 2003).…”
Section: Sideróferosunclassified